Micro-Credentials and Skills: Towards A Paradigm Shift in Reskilling? - Karachalios, George; Papadakis, Nikos (Advances in Social Sciences Research Journal, 2023)
The paper deals with the role of Training and Reskilling, as part of active employment policy, specifically focusing on the dynamics of micro-credentials. It begins with a brief overview of the dominant trends in the Labour Market in order to proceed with the analysis of the role of Skills, within this (rapidly changing) context. Given the abovementioned, the paper focuses on the role of the micro-credentials in Reskilling, (flexibly) building individual skills-repertoire and feed-backing the existing accreditation-certification practices and patterns. It provides a critical overview of the state-of-play regarding the rising trend towards Micro-Credentials and their association with Skills, Training and Reskilling.